2019
DOI: 10.15446/revfacmed.v67n3.73245
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic, criminal and forensic characteristics of a sample of female children and adolescents murdered in Brazil. 2010-2016

Abstract: Introduction: In Brazil, violence, regardless of the type, is the leading cause of death in adolescents and young adults.Objective: To describe the characteristics of the homicides in which female children and adolescents were the victims based on the autopsy reports recorded in the morgue of the city of Porto Alegre, Brazil.Materials and methods: Cross-sectional study in which 70 autopsy reports of girls and female adolescents who were killed between January 2010 and December 2016 were analyzed. The cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…During the containment measures and epidemiological emergency management of the COVID-19 pandemic, some studies have shown that the circumstances of social distancing increased social problems and brought new stressors, including risks to physical and psychological health, isolation and loneliness, many school and business closures, economic vulnerability, and job losses (Henson, 2020; Usher et al, 2020). Due to these reasons, women were more vulnerable to the risk of domestic violence, as the victims remained confined in the same place with their aggressors, making it difficult to seek help (John et al, 2020; Machado-Rios et al, 2020; Pattojoshi et al, 2021). The quarantine also reduced the options for women to seek immediate assistance, as did the limited health infrastructure, and social and legal services (Fawole et al, 2021; John et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the containment measures and epidemiological emergency management of the COVID-19 pandemic, some studies have shown that the circumstances of social distancing increased social problems and brought new stressors, including risks to physical and psychological health, isolation and loneliness, many school and business closures, economic vulnerability, and job losses (Henson, 2020; Usher et al, 2020). Due to these reasons, women were more vulnerable to the risk of domestic violence, as the victims remained confined in the same place with their aggressors, making it difficult to seek help (John et al, 2020; Machado-Rios et al, 2020; Pattojoshi et al, 2021). The quarantine also reduced the options for women to seek immediate assistance, as did the limited health infrastructure, and social and legal services (Fawole et al, 2021; John et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Restricted access to victim support services during this period is also an aspect that should be noted (de Paz et al, 2020). In addition to the decrease in police interventions, the limitation of health services, and the courts being closed resulted in a difficulty to report violence cases and contributed to impunity (John et al, 2020; Machado-Rios et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis for increased female homicides in younger groups is the abuse of alcohol and other substances by the younger generation of men, which makes them victims and perpetrators of multiple forms of violence, including gender-based violence [9,40]. Lethal domestic violence implies a significant loss of life years and a reduction in overall life expectancy in affected families [41].…”
Section: Plos Onementioning
confidence: 99%
“…Fakta-fakta yang demikian terjadi di lingkup masyarakat merupakan permasalahan yang erat kaitannya dengan anak (Machado-Rios, 2019). Dalam hubungan sosial, pendidikan, dan pergaulan seorang anak sangat rentan dipengaruhi oleh berbagai faktor yang mendorong terjadinya tindak pidana kekerasan seksual, utamanya anak sebagai pelaku (Denne, 2023;Kulik, 2021;Mulyadi, 2018;Richards, 2022).…”
Section: Pendahuluanunclassified